Internal structure of the 85°E ridge, Bay of Bengal: Evidence for multiphase volcanism. (February 2017) - Ismaiel, M.; Krishna, K.S.; Srinivas, K.; Mishra, J.; Saha, D.
Abstract: The 85°E Ridge, located in the Bay of Bengal of the northeastern Indian Ocean is an enigmatic geological feature as it possesses unusual geophysical signatures. The ridge's internal structure and mode of eruptions are unknown due to lack of deep seismic reflection and borehole data control. Here, we analyze 10 km of long-streamer seismic reflection data to unravel the ridge's internal structure, and thereby to enhance the understanding of how the ridge was originated and grew over a geologic time. Seismic facies analysis reveals the ridge structure consisting of volcanic vent and several stratigraphic units including packs of prograding clinoforms. The clinoform sequences are interpreted as volcanic successions, and led to the formation of lava-delta fronts. Interpreted features of lava-fed deltas and intervening erosional surfaces, and mass flows along ridge flanks suggest that the 85°E Ridge is a volcanic construct, and was built by both subaqueous and multiphase sub-marine volcanism during the Late Cretaceous (approximately from 85 to 80 Ma). At later time, from Oligocene-Miocene (∼23 Ma) onwards the ridge was buried under the thick sediments of the Bengal Fan system. Highlights: High-quality seismic data image the internal structure of the 85°E Ridge. Volcanic conduit and series of lava deltas identified within the 85°E Ridge reveal nature of the ridge. Tectonic model proposed for the emplacement of the 85°E Ridge and its growth through time.